Stock flow adjustments in sovereign debt dynamics: the role of fiscal frameworks - António Afonso; Jo\~ao Tovar Jalles (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We assess, via system GMM, how Stock Flow Adjustments (SFA) affect the debt-to-GDP ratio in 65 countries (covering developed and emerging and low-income countries) between1985-2014. We find that SFAs positively contribute to the change in the debt-to-GDP ratio with a coefficient close to one. The existence of fiscal rules with monitor compliance contributes to lower the debt level. The fall in the debt ratio due to fiscal rules before the crisis was between 1.7%-4.2% of GDP while after the crisis, revenue and debt-based rules did not contribute to the reduction of debt, which was reinforced with large SFAs.
Keywords: 330